Analysis of Depreciation Calculation of Fixed Assets According to SAK-ETAP and Tax Regulations on Credit Cooperatives CU Sawiran Malang: Penyusutan - Laurentia Sunyi Asmara; Revi Arfamaini (Universitas Katolik Darma Cendika, 2026)
Fixed assets play a crucial role in a company's operational performance. The importance of fixed assets necessitates depreciation calculations in accordance with Financial Accounting Standards (SAK-ETAP) and the Tax Law in financial statements. One factor contributing to the differences is the accounting treatment of fixed assets, particularly regarding depreciation calculations. Depreciation expense for fixed assets can be calculated using depreciation methods consistent with Financial Accounting Standards (SAK-ETAP) and tax regulations. The depreciation method according to Financial Accounting Standards (SAK-ETAP) is used to assess a company's performance and financial condition, while the depreciation method based on tax regulations is used for tax purposes. This study uses qualitative data with primary data as its source, obtained directly from the research object. The data was collected from the Sawiran Credit Cooperative in Malang. The results show significant differences in depreciation calculations between commercial and fiscal depreciation. These differences are primarily due to differences in the basis for measuring depreciation. The resulting depreciation differences impact commercial and fiscal profit. Because the fiscal depreciation burden is greater than the commercial depreciation burden, the cooperative's fiscal profit is lower than its commercial profit